Skinhead : a novel - Bennett, Jay. (New York : F. Watts, 1991)
A plea from a dying man he has never seen before involves nineteen-year-old Jonathan in a life-and-death struggle with white-supremacist skinheads.
Booklist.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Mystery and detective stories; White supremacy movements -- Fiction; Mystery fiction; White supremacy movements -- Fiction